Multidimensional Challenges in the Implementation of the Acute Appendicitis Clinical Pathway - Arsil, Firli Yan; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (FORIKES, 2025)
Acute appendicitis is a common cause of acute abdominal pain that requires immediate intervention to prevent complications, especially among vulnerable groups such as children and the elderly. The clinical pathway is used to standardize care, improve efficiency, and reduce costs. This study aimed to analyze the implementation of the acute appendicitis clinical pathway at Pertamina Hospital Pangkalan Brandan. The research used a qualitative phenomenological approach involving six informants (two key, two main, and two supporting). Data were collected through observation, in-depth interviews, and document review, then analyzed descriptively through data reduction, presentation, and conclusion drawing. The results showed that the implementation of the acute appendicitis clinical pathway still faces challenges in unstructured interprofessional communication, limited human resources such as case managers and clinical pharmacists, and the absence of an adequate information and logistics system. Resistance also occurs due to low understanding, entrenched old practices, and lack of incentives. Internal evaluations have not significantly influenced behavioral change, while supervision and inter-unit coordination remain weak. As conclusion, the implementation of the acute appendicitis clinical pathway at Pertamina Hospital Pangkalan Brandan faces interrelated, multidimensional challenges across communication, resources, disposition, and bureaucratic structure aspects.Keywords: hospital; clinical pathway; acute appendicitis